Resilience Enhancement Strategies for Energy Systems in the Face of Natural Calamities and Cyber Threats: A Comprehensive Review - Mostafa Shabanian-Poodeh; Rahmat-Allah Hooshmand; Miadreza Shafie-Khah; Pierluigi Siano (IEEE Access)
Energy systems and their related technologies are susceptible to natural extreme events, categorized as high-impact low-probability (HILP) events, posing a significant threat to their reliable functioning. Gas-to-power (G2P) and power-to-gas (P2G) technologies establish a bidirectional interface between these energy systems, leading to the creation of integrated power and natural gas systems (IPGS) as energy systems. Due to their extensive geographical coverage, energy systems are particularly vulnerable to severe damage from natural calamities. Given the growing interest and research focus on energy systems resilience, this comprehensive review meticulously navigates the intricate terrain of resilience differentiation, offering a detailed roadmap fortified by insights from significant instances of grid failures and weather-driven contingencies. The review examines preemptive cyber security fortifications and strategic planning imperatives, scrutinizing each aspect with conviction and clarity. Temporally stratified into long-term and short-term horizons, it not only delineates prevailing approaches and methodologies but also identifies emerging trends poised to shape the future landscape of resilience enhancement. This paper provides an exhaustive review of existing research on the resilience of energy systems, introducing a visual framework for comparing different studies and facilitating easy understanding through multiple figures. Since uncertainties play a crucial role in decision-making within this field, this paper broadly explores methods for addressing them as presented in previous studies. Furthermore, the literature is meticulously classified to offer a clear and organized overview, highlighting the impact of HILP events, such as natural disasters and cyber-attacks, on energy systems resilience. This review underscores the critical need to fortify energy systems, emphasizing its importance as a crucial component of integrated energy systems in preparing for the continuous impact of natural disasters in future research.